Oral hairy leukoplakia in the buccal mucosa of a healthy, HIV-negative patient - Gürel, Gülhan; Şahin, Sevinç; Aytekin, Betül; Çölgecen, Emine (Journal of Surgery and Medicine, 2018)
Oral hairy leukoplakia (OHL), first described in 1984, is an Epstein-Barr virus lesion located laterally in the tongue and manifesting as a white, asymptomatic mucosal plaque which cannot be removed by scraping. OHL is more commonly observed in HIV-positive patients, in immunosuppressed patients after kidney, heart, liver and bone marrow transplantation, in hematological malignancies such as multiple myeloma, and in patients undergoing systemic or topical steroid therapy. OHL has rarely been reported in healthy patients who are not immunosuppressive. The case of an otherwise healthy, HIV-negative 24 year-old woman with OHL lesions in the buccal mucosa is presented here because of its rarity.